A Retrospective Study Establishing Pre-Pandemic Demographic Baselines for United States Source Plasma Donors. (October 2022) - Rosa-Bray, Marilyn; Bounpheng, Mangkey A.; Wisdom, Charlene; Gierman, Todd; Becker, Mark; Crookston, Kendall P.
Background: The COVID-19 pandemic highlighted plasma as a strategic resource with continually increasing demand. Demographic data for plasma donors are limited compared with blood donors. Increased information regarding pre-pandemic donor demographics may serve as a baseline for evaluation of post-pandemic practices. OBJECTIVES: This study asked the question, "What were the demographics of source plasma donors in the US compared to the general population and how did these change over a five-year period preceding the pandemic?" STUDY DESIGN: Donor demographic data were retrospectively analyzed for the years 2014, 2016 and 2018 from a network of US plasma centers. METHODS: Routine demographic data obtained prior to source plasma collection from all plasma donors at Grifols US centers were retrospectively analyzed. Donor screening and eligibility requirements were standardized across all donor sites and met all donor eligibility requirements (Code of Federal Regulations: 21 CFR part 600). During each calendar year, only data from the first donation in that year were included with each cohort year. RESULTS: This study included 1, 303, 049 unique donors. Donors were predominantly young adult males, although females increased from 37.4% to 41.6%. Caucasians constituted the highest proportion, followed by African American and Hispanic donors. Demographics were generally stable, but the 2018 cohort and the US population exhibited significantly different age, race/ethnicity, and sex profiles. Of 2014 donors, 9.0% returned in all three years studied (2014-2016-2018), with a higher return rate of 16.0% observed for donors returning in just two of the years (2014-2016). Multiyear donors were predominantly male and African American. CONCLUSION: US plasma donor demographics over a five-year period (2014-2018) showed generally consistent characteristics but differed from the general US population. Multiyear donors were demographically distinct from single-year donors. These data serve as a snapshot of the US source plasma donor base prior to the COVID-19 pandemic.